Unifying educational systems : leadership and policy perspectives - Burrello, Leonard C., 1942-; Sailor, Wayne; Kleinhammer-Tramill, Jeannie (Taylor and Francis, 2012)
Unifying Educational Systems encourages leaders to move beyond the traditional forms and rituals of leadership for special education that are caught within traditional definitions of a continuum of services. Grounded in public policy debates, research on teaching and learning, and an emerging consensus throughout the leadership community that calls into question our current practices, chapters in this volume provide a discussion of the purpose, principles, and paradoxes extant in the implementation of current special education policy. Chapter authors discuss how students are curren.